Theories and theorizing in public administration: A systematic review - Fabian Hattke; Rick Vogel (Public Administration Review, 2023)
Theories and theorizing are central to scholarship on public administration (PA). Only a few attempts have been made to review the theories applied in PA broadly and systematically, to take stock of the theoretical repertoire, and to engage scholars in critical reflection on how they “do” theorizing. This study analyzes the theoretical landscape of PA scholarship with a novel combination of bibliometrics and natural language processing. A “tree of theories” shows how 150 theories merge into one body of scholarship, with 15 theories at the core. The theories vary considerably in terms of disciplinary background, methodological choices, geographical settings, author diversity, and reach beyond academia. While the results indicate the plurality and vitality of the field, they also raise concerns about how core theories show limited geographical dispersion and low societal relevance. These concerns are further fueled by an apparent schism between micro and macro theories.
Keywords: 340